Performance of mutual funds in emerging markets - Motaung, Naledi Molepa (University of the Witwatersrand, Johannesburg, 2024)
This study delves into the dynamics of mutual fund performance within the BRICS economies, underpinned by theoretical frameworks like Modern Portfolio Theory and the Mutual Fund Theorem. The study aims to provide a comprehensive examination of mutual fund architectures, classifications, and their inherent advantages, alongside the diverse factors shaping investment choices. The study further aims to assess and juxtapose the effectiveness of BRICS mutual funds, by deploying established measures such as Jensen's Alpha, Sharpe ratio, Treynor ratio, and the Fama-French and Carhart factor models. These measures facilitate a deeper comprehension of returns, especially when comparing portfolios with analogous risk profiles, underscoring the diverse sources of returns. The findings indicate that Chinese mutual funds are distinguished by superior risk- adjusted returns over a period of one to five years, signifying a more proficient market. The Fama-French three factor model regression results exhibited a positive correlation between market activity and returns, with Indian funds showing heightened market sensitivity. While the Carhart model introduces momentum as a novel component, its contribution to explaining mutual fund performance is minimal. The models' limited R- squared values imply the existence of additional influential factors not encapsulated by both the three and four factor models. The juxtaposition of performance measures and factor models exposes a consistent theme of market sensitivity and risk-adjusted performance, albeit with misalignment due to their measurement of different risk dimensions. Notably, the Emerging Markets Four-Factor Model emerges as a more refined tool, offering an enhanced comprehension of the forces driving performance in BRICS, potentially reconciling the disparities observed with the more traditional performance metrics. Overall, the research contributes to the understanding of mutual fund performance in emerging markets, particularly in the BRICS economic bloc. It highlights the opportunities and challenges faced by investors and provides insights into the factors that influence mutual fund returns in these dynamic and diverse markets.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Finance and Investments to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: MUTUAL FUNDS; BRICS; PERFORMANCE; EMERGING MARKETS; UCTD; SDG-8: Decent work and economic growth